Inherited anti-thrombin deficiency in a Malay-Malaysian family: a missense mutation at nucleotide g.13267C>A aka anti-thrombin Budapest 5 (p.Pro439Thr) of the SERPINC 1 gene - A.Talib, Norlelawati; Ismail, Rusmawati; Muhammad, Siti Aeshah @ Naznin; O., Nur Nadia; R., Rizqan Aizzani; Abd. Wahab, Noraziana (Malaysian Medical Association, 2014)
OBJECTIVE: